(NtEKTONIKA sEWERNOGO pRI^ERNOMORXQ (B/s - (NdOWGALX(B, (N`(B.(Nm(B.s; (NzNAMENSKAQ(B, (Nt(B.(Na(B.s; (NiNSTITUT GEOLOGI^ESKIH NAUK an ussrs ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 158-163 (195 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NtEKTONIKAs -- (NsEWERNOE pRI^ERNOMORXEs